ANALISIS PENGEMBANGAN KARIR PEGAWAI PADA KANTOR DINAS PENDAPATAN DAERAH PROVINSI SULAWESI TENGAH - Muhajir, Muhammad (Katalogis, 2015)
The research aims at finding out and analyze officersâ€™ carrier development at regional income office of Central Sulawesi Province.Â This was a qualitative research with 4 informants. The technique of data collection was interview and documentation. The data analysis was (1) editing, (2) classifying, (3) interpreting, and (4) drawing conclusion and suggestion. The research result reveals that: (1) carrier development at regional income office is not maximal yet due to the unfairness treatment. It was proved with interview result from all informants stating that carrier development mechanism needs to be improved in the future, (2) carrier development seen from concerns was not maximal as well, it was proved with inequity of carrier development of officers, (3) from promotion aspect, carrier development was the same as the first result, (4) from interest aspect, the carrier development is already maximal because all officers need to have satisfactory carrier, and (5) from satisfactory aspect, the carrier development is not maximal due to the difference level of satisfactory among the officers and it is supported by interview result from informants.